Use of Long-Distance Migration Patterns of an Endangered Species to Inform Conservation Planning for the World's Largest Marine Protected Area - Nicole Esteban (Conservation Biology, 2014)
Large marine protected areas (MPAs), each hundreds of thousands of square kilometers, have been set up by governments around the world over the last decade as part of efforts to reduce ocean biodiversity declines, yet their efficacy is hotly debated. The Chagos Archipelago MPA (640,000 km2) (Indian Ocean) lies at the heart of this debate. We conducted the first satellite tracking of a migratory species, the green turtle (Chelonia mydas), within the MPA and assessed the species’ use of protected versus unprotected areas. We developed an approach to estimate length of residence within the MPA that may have utility across migratory taxa including tuna and sharks. We recorded the longest ever published migration for an adult cheloniid turtle (3979 km). Seven of 8 tracked individuals migrated to distant foraging grounds, often 1000 km outside the MPA. One turtle traveled to foraging grounds within the MPA. Thus, networks of small MPAs, developed synergistically with larger MPAs, may increase the amount of time migrating species spend within protected areas. The MPA will protect turtles during the breeding season and will protect some turtles on their foraging grounds within the MPA and others during the first part of their long-distance postbreeding oceanic migrations. International cooperation will be needed to develop the network of small MPAs needed to supplement the Chagos Archipelago MPA.